Crassatella rubrolineata Turton, 1932, as a replacement name for Crassatella sowerbyi Lamy, 1917 non Wood, 1871 (Bivalvia, Crassatellidae), and a revision of Wood’s subspecies of C. sowerbyi - Collins, Katie S. (Zootaxa, 2024)
Resolving and disambiguating the many names given to fossil and Recent Crassatellidae is sometimes a knotty problem, exacerbated by the subtle differences between taxa and many applications of simple descriptive specific epithets (‘sulcata’, ‘rostrata’, ‘compressa’ etc.) leading to homonyms requiring resolution. The common decision to (perhaps) soften the blow of replacing someone’s name by erecting an eponym as a replacement to honour them has led to further unresolved homonyms and taxonomic ambiguities. One such case is addressed here. In this paper I resolve the homonymy of Crassatella sowerbyi Wood with Crassatella sowerbyi Lamy by replacing Lamy’s name with the available junior synonym C. rubrolineata Turton. Further, I revise the suite of taxa considered by Wood to be of subspecific rank within C. sowerbyi: I synonymise C. s. var. obesa with C. sowerbyi, and elevate C. s. var. semilaevis and C. s. var. hantoniensis to full specific rank. Detailed descriptions and illustrations are provided for all species.